Empowering organizations through corporate social responsibility - Wolf, Ruth; Thiel, Monica; Issa, Theodora (Hersey Business Science Reference, 2014)
This book addresses the implementation of businesses' ethical standards in both emerging and advanced economies, interpreting the social impact of this issue in a global context by highlighting case studies, interdisciplinary perspectives, and strategies in business management
A volume in the Advances in Business Strategy and Competitive Advantage (ABSCA) Book Series
Keywords: Empresas -- Responsabilidad social; Planificación estratégica; Ética de los negocios; Libros electrónicos